Recursive renormalization of the singlet one-pion-exchange plus point-like interactions - Timoteo, V. S.; Frederico, T.; Delfino, A.; Tomio, L. (Elsevier B.V., 2005)
The subtracted kernel approach is shown to be a powerful method to be implemented recursively in scattering equations with regular plus point-like interactions. The advantages of the method allows one to recursively renormalize the potentials, with higher derivatives of the Dirac-delta, improving previous results. The applicability of the method is verified in the calculation of the 1 So nucleon-nucleon phase-shifts, when considering a potential with one-pion-exchange plus a contact interaction and its derivatives. The S-1(0) renormalization parameters are fitted to the data. The method can in principle be extended to any derivative order of the contact interaction, to higher partial waves and to coupled channels. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: renormalization; renormalization group; nonrelativistic scattering theory